The polemical works of 'Ali al-Tabari - Ṭabarī, ʻAlī ibn Sahl Rabbān, active 9th century. (The History of Christian-Muslim Relations, 2016)
Acknowledged as a leading medical expert in his day, and secretary to a succession of caliphs in the mid-ninth century, the Nestorian Christian ʿAlī ibn Rabban al-Ṭabarī converted to Islam around the age of 70. He then wrote Radd ʿalā l-Naṣārā , a recantation of his former faith, and Kitāb al-dīn wa-l-dawla , a defence of the Prophet Muḥammad based substantially on biblical proof-texts. The range of arguments he produced against the soundness of his former faith in these two works influenced sections of Islamic scholarship for many centuries. These new editions and translations of his works are based on all the available evidence for the texts, accompanied by extensive introductions and studies of their place in Islamic thought.